HR 3 Tesla MRI for the Diagnosis of Endolymphatic Hydrops and Differential Diagnosis of Inner Ear Tumors – Demonstrated by two Cases with Similar Symptoms - Homann, G.; Fahrendorf, D.; Niederstadt, T.; Nagelmann, N.; Heindel, W.; Lütkenhöner, B.; Böckenfeld, Y.; Basel, T.; Vieth, V. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
The synchronous appearance of different inner ear pathologies with a nearly equivalent clinical manifestation such as Menière’s disease and vestibular schwannoma is very rare but leads to a relevant dilemma concerning therapy options. MRI is the method of choice to detect intralabyrinthine tumors. Since endolymphatic hydrops is considered the morphological equivalent of Menière’s disease, magnetic resonance imaging including hT2w-FLAIR sequences 4 h after i. v. administration of gadolinium-based contrast agents (GBCA) allows the diagnosis and grading of endolymphatic hydrops in vivo synchronous to diagnosis and monitoring of ILT. To this day, only a few cases of intralabyrinthine schwannoma could be shown to appear simultaneously with endolymphatic hydrops by MRI, but to our knowledge the dedicated distinction of endolymphatic space has not been previously demonstrated. The aim of this work was not only to detect the coincidence of endolymphatic hydrops and vestibular schwannoma, but also to differentiate tumor tissue from endolymphatic space by 3 Tesla MRI. This enables therapy options that are originally indicated for Menière’s disease. The aim of this work was to describe the feasibility and usefulness of endolymphatic hydrops MRI on intralabyrinthal tumors in a special case of intravestibular schwannoma to demonstrate the high clinical relevance and impact in therapeutic decision-making for the synchronous appearance of endolymphatic hydrops and intralabyrinthine tumors. Therefore, we present a typical case of Menière's disease in contrast to a patient with an intralabyrinthine schwannoma and Menière-like symptoms.Citation Format:• Homann G, Fahrendorf D, Niederstadt T et al. HR 3 Tesla MRI for the Diagnosis of Endolymphatic Hydrops and Differential Diagnosis of Inner Ear Tumors – Demonstrated by two Cases with Similar Symptoms. Fortschr Röntgenstr 2014; 186: 225 – 229
Keywords: head/neck; ear; MR imaging; hearing loss; schwannoma